Pengukuran Variabilitas Co2 dan Analisis Dampak Perubahan Iklim (Studi Kasus: Semarang) - R Gernowo; A Kusworo; Z Arifin (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The increasing emission of CO2 in the air has led to the need to measure the gas content on a regular basis. The gas accumulates slowly in the layers of Earth's atmosphere. However, this need is constrained by a number of issues that later affect the accuracy of the mapping which includes the continuously circulating gas in the atmosphere. Researchers suspect that the amount of CO2 and other gases is getting higher due to the many additional human produced carbon emissions from burning fossil fuels. In this study climate change analysis was conducted in Semarang. The study looks deeper in the CO2 variability data from referencestudies and performs analysis of climate data from rainfall and CO2 measurement data of Semarang.